An Exploratory Study on Corporate Governance From Neuro-Governance Lenses in the Malaysian Context - Ivascu, Larisa; Pavel, Codruta Daniela; Sarfraz, Muddassar; Arulanandam, Benedict Valentine*; Tan, Hong Yip (Frontiers Media, 2022)
Our minds are powerful, creative, forceful, and strong, controlling our thinking and behaviors. A series of high-profile accounting and financial scandals have been revealed in the past few decades, and the Enron case was the most representative of them all. Corporate decision-makers have traditionally enjoyed high remunerations, compensations, and social status. Hence, the underlying rationales and motivation drivers that motivate managers to conduct unethical behaviors have always been a heightened concern. This research aims to delineate the narratives of corporate governance misconducts and the underlying rationales of these unethical behaviors. This study incorporates independent variables of neuro-accounting, neuroeconomics, neuro-ethics, and human nature using a qualitative methodology. From this study, the social norm of fairness showed that the human nature of greed and selfishness would motivate corporate decision-makers to engage in any exchange that could benefit themselves, although it is unethical and illegal. Second, neuroeconomics revealed that scarcity of economic resources, level of risks and uncertainties, and expected rewards could be the factors that motivate managers to conduct unethical behaviors, especially when their remunerations are tightly linked to company performances. Third, neuroethics shows that managers who lack moral values, have unstable emotions, and possess negative moral intuitions or personal assumptions could be more likely to pursue their interests at the cost of others. Lastly, neuro-governance also proved that self-benefits and financial incentives will usually be the priority and would be a motivating factor for misconduct.